2020
DOI: 10.3390/ani10122215
|View full text |Cite
|
Sign up to set email alerts
|

Diet Composition of the Wild Stump-Tailed Macaque (Macaca arctoides) in Perlis State Park, Peninsular Malaysia, Using a Chloroplast tRNL DNA Metabarcoding Approach: A Preliminary Study

Abstract: Understanding dietary diversity is a fundamental task in the study of stump-tailed macaque, Macaca arctoides in its natural habitat. However, direct feeding observation and morphological identification using fecal samples are not effective and nearly impossible to obtain in natural habitats because this species is sensitive to human presence. As ecological methods are challenging and time-consuming, DNA metabarcoding offers a more powerful assessment of the diet. We used a chloroplast tRNL DNA metabarcoding ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In addition to traditional methods based on direct observations and feeding traces, molecular approaches provide further opportunities to detect rare dietary items, revealing a more complete picture of cryptic and rare species' nutritional ecology (Ait Baamrane et al, 2012;Bradley et al, 2007;Goldberg et al, 2020;Hibert et al, 2013;Nawaz et al, 2019;Osman et al, 2020;Quéméré et al, 2013;Valentini et al, 2009). The approach is scalable to many individuals, is not biased towards habituated or approachable individuals, and provides data which can be compared across species (Kartzinel et al, 2019).…”
Section: Molecular Analyses Complement Field Observations Of Grauer's Gorilla Dietmentioning
confidence: 99%
“…In addition to traditional methods based on direct observations and feeding traces, molecular approaches provide further opportunities to detect rare dietary items, revealing a more complete picture of cryptic and rare species' nutritional ecology (Ait Baamrane et al, 2012;Bradley et al, 2007;Goldberg et al, 2020;Hibert et al, 2013;Nawaz et al, 2019;Osman et al, 2020;Quéméré et al, 2013;Valentini et al, 2009). The approach is scalable to many individuals, is not biased towards habituated or approachable individuals, and provides data which can be compared across species (Kartzinel et al, 2019).…”
Section: Molecular Analyses Complement Field Observations Of Grauer's Gorilla Dietmentioning
confidence: 99%
“…For long-tailed macaque population in the Recreational Park of Cenderawasih Cave, F. superba also accounted for a significantly greater proportion of the macaque’s diet. F. superba was the main plant diet consumed by another macaque species, Macaca arctoides inhabiting Perlis State Park, Wang Kelian, Perlis, Malaysia ( Osman et al 2020 ). Primates that live in more marginal habitats depend highly on limited critical food resources, such as figs, that play an important role in nourishing frugivores through periods of natural and imposed food shortage ( Kinnaird et al 1999 , Tweheyo and Lye 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on the dietary composition of wild stump-tailed macaques indicated that they mainly consume plant materials from the forest [19]. Unlike its cousins, the long-tailed macaques and pig-tailed macaques are more often spotted at human concentrated areas, and at times orchards, plantations, and even garbage collection sites.…”
Section: Macaques Involvement In Human-wildlife Conflictsmentioning
confidence: 99%